Determining Evolving of Rising Issues in Social Network - Kausalya, R; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
This paper presents an intelligent news stream representation that reveals rising subjects in dynamic advanced content archives. The exhibited approach consolidates a few visual analogies and can be effortlessly adjusted to present multi-source social media datasets. In the connection of this work, we talk about different routines on the other hand improving visual interfaces on the other hand getting to amassed media representations. We consolidate falling squares with bar diagrams and arcs, in any case keep these parts unmistakably separated in diverse zones of the display. The circular segment metaphor the other hand is adjusted and improved with interactive controls to help clients understand the dataset’s underlining meaning. The paper portrays the execution of the model and talks about plan issues with a particular accentuation on visual analogies to highlight covered up relations in advanced content. We finish up with a summary of the lessons learnt and the incorporation of the representation part into the Media Observe on Atmosphere Change (www.ecoresearch.net/climate), a open Web entry that totals ecological information from a variety of online sources counting news media, web journals and other social media such as Twitter, YouTube and Facebook.